Biosynthesis and recent advances in production of bacterial cellulose - Donini, Ígor A.N. [UNESP]; de Salvi, Denise T.B. [UNESP]; Fukumoto, Fabiana K. [UNESP]; Lustri, Wilton R.; Barud, Hernane S. [UNESP]; Marchetto, Reinaldo [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney J.L. (Ecletica Quimica, 2010)
The present paper discusses the recent advances about the biosynthesis and production of bacterial cellulose (BC), from gram-negative, aerobic and acetic acid Gluconcetobacter xylinus (Gx). The BC differs from his vegetal pair, mainly due his feature of nanometric fibers, as opposed to micrometric feature of vegetal cellulose, are extruded through the cellular wall of Gx, thereby the macroscopic structure of BC is mechanically and physically more resistant, open big opportunities of biological and technological applications, apart from that obtained by vegetal cellulose. The actual challenge is in the grown of production of BC, which deals a superior understanding of his biosynthesis, to makes possible a later genetic-biochemical manipulation derived from recent advances in molecular biology. Are related works using the BC for production of composites and also what is being done of more actual with this biological material.
BiossÍntese e recentes avanÇos na produÇÃo de celulose bacteriana
Keywords: Advances; BacterialCellulose; Biosynthesis; Gluconacetobacter